Implementasi Permainan Bola Besar Terhadap Positive Youth Development - Akmal Tri Nuralim; Lukmannul Haqim Lubay; Gano Sumarno (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the effect of implementing modified large-ball games on the improvement of Positive Youth Development (PYD) among elementary school students. The method used was a quantitative approach with an experimental method employing a one-group pretest–posttest design. The research subjects were elementary school students selected through purposive sampling. The treatment consisted of implementing modified large-ball games over 14 physical education sessions, involving adjustments to rules, number of players, game duration, and the integration of values such as responsibility, cooperation, empathy, and sportsmanship. The research instrument used was the Positive Youth Development Inventory (PYDI), which measures five main dimensions of PYD: competence, confidence, connection, character, and caring. Data were analyzed using prerequisite tests and hypothesis testing through the Paired Sample t-Test. The results showed a significant improvement in all aspects of Positive Youth Development after the implementation of the modified large-ball games. The significance value obtained was less than 0.05, indicating a positive and significant effect on the development of PYD among elementary school students. In conclusion, the implementation of structured and developmentally appropriate modified large-ball games in physical education learning is proven to be an effective strategy for enhancing students’ competence, self-confidence, positive social relationships, character, and social caring. Keywords: Elementary School Students, Modified Large-Ball Games, Physical Education, Positive Youth Developmentd